On the role of the difference in surface tensions involved in the allosteric regulation of NHE-1 induced by low to mild osmotic pressure, membrane tension and lipid asymmetry - Pang, Vincent; Counillon, Laurent; Lagadic-Gossmann, Dominique; Poet, Mallorie; Lacroix, Jérôme; Sergent, Odile; Khan, Raheela; Rauch, Cyril (Humana Press, 2012)
The sodium-proton exchanger 1 (NHE-1) is a membrane transporter that exchanges Na+ for H+ ion across the membrane of eukaryotic cells. It is cooperatively activated by intracellular protons, and this allosteric regulation is modulated by the biophysical properties of the plasma membrane and related lipid environment. Consequently, NHE-1 is a mechanosensitive transporter that responds to osmotic pressure, and changes in membrane composition. The purpose of this study was to develop the relationship between membrane surface tension, and the allosteric balance of a mechanosensitive transporter such as NHE-1. In eukaryotes, the asymmetric composition of membrane leaflets results in a difference in surface tensions that is involved in the creation of a reservoir of intracellular vesicles and membrane buds contributing to buffer mechanical constraints. Therefore, we took this phenomenon into account in this study and developed a set of relations between the mean surface tension, membrane asymmetry, fluid phase endocytosis and the allosteric equilibrium constant of the transporter. We then used the experimental data published on the effects of osmotic pressure and membrane modification on the NHE-1 allosteric constant to fit these equations. We show here that NHE-1 mechanosensitivity is more based on its high sensitivity towards the asymmetry between the bilayer leaflets compared to mean global membrane tension. This compliance to membrane asymmetry is physiologically relevant as with their slower transport rates than ion channels, transporters cannot respond as high pressure-high conductance fast-gating emergency valves.